The Impact of Nurse Empathy in Hospitals Nursing Services - Atanay, Ruth Susana; Dwidiyanti, Meidiana; Dwiantoro, Lucky (Universitas Jenderal Achmad Yani Yogyakarta, 2023)
Background: Complaints about nursing services because some nurses do not care, lack communication with patients, and are indifferent to patients, this is because nurses are not empathetic, so empathy is needed in current nursing actions to improve the quality of nursing services, the outcome of which is patient satisfaction.Objective: This article aims to determine the impact of empathy on nursing services in hospitals. Methods: The literature search used keywords “empathy” OR “nurse” or “nursing service” OR “hospital”. With systematic review analysis and meta Analyzes for scoping review (PRISMA -SR).Results: After screening consisting of 6 articles which summarized the impact Empathy is very important in improving nursing services, it was found that there were 3 impacts of empathy, namely: (1) increasing the therapeutic relationship between nurse-patient obtained from 3 articles, (2) increasing patient satisfaction obtained from 2 articles (3) reduce the psychological impact of the patient 1 article. Conclusion: There are 3 impacts of empathy consisting of (1) Increasing the therapeutic relationship between nurse-client. (2) Increasing patient satisfaction (3) Reducing the psychological impact of the patient